Permanent Deformation Behavior of Crushed Rock Base (CRB) as Highway Base Course Material - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (International Society of Asphalt Pavements (ISAP), 2010)
This paper aims to report the permanent deformation behavior of the Crushed Rock base (CRB) layer under traffic loads using repeated load triaxial (RLT) tests simulating various conditions of basecourse, in order to determine the limit use and dynamic response of CRB. The main deterioration of flexible road surface is rutting because of insufficient material strength. As is well known, current pavement design does not consider permanent deformation of basecourse material, it only requires the index properties and bearing capacity of it. Although an adequate bearing capacity material was placed in the pavement structure, several roads were still damaged. For pavement design criteria, it is not enough to consider only the permanent deformation at the top of the subgrade layer but also the plastic strains taking place in base, subbase and even the asphalt layer which contribute to the overall rutting appearing in the thin asphalt surface. Currently, the plastic deformation characteristics of CRB as a base material is not yet clearly understood.It results from an accumulation of the plastic strain of each cyclic loading cycle up to failure. In this study, the shakedown concept was therefore utilized to describe the permanent deformation characteristic of CRB. The plastic shakedown limit is used to predict the failure criteria at a certain level of the accumulated plastic deformation in the unbound granular material (UGMs) layer. However, the permanent deformation characteristic of UGMs is also dependent on the applied stress levels. The outcome in this study is that the limits of a working stress level and the plastic shakedown limit of CRB were defined.